Sea surface height measurements using a low-cost GNSS buoy with multiple GNSS receivers. (1st June 2023) - Di, Mingwei; Guo, Bofeng; Ren, Jie; Li, Mengyuan; Chen, Xiyuan; Zhang, Anmin
Abstract: Accurate Sea surface height (SSH) measurements are important for global climate change and sea level rise monitoring. Satellite altimeters can provide global coverage observations but with coarse temporal and spatial resolution, while tide gauges offer high-precision measurements but are limited to coastal regions. The advent of Global Navigation Satellite System (GNSS) buoys bridge the gap between the tide station and the satellite altimeter, which realize continuous and reliable absolute SSH measurements in the coastal zone. However, most of buoys are equipped with GNSS geodetic receivers and antennas, which are expensive and with high power consumption. The emergence of low-cost receivers has been applied in fields such as autonomous driving and disaster monitoring, yet low-cost receivers suffer precision limitations due to signal quality issue in the harsh marine environment. To solve the reliability issue of low-cost receivers in SSH measurements, firstly, a low-cost buoy platform with four dual-frequency receivers is designed in this contribution. GNSS antennas are installed on the four corners of a square with a side length of 1.180 m, and the total power consumption is less than 4 W. Additionally, a robust outlier detection method, the Geometric Constraint algorithm, is proposed to improve the reliability and accuracy of GNSS SSH results. The performance of our buoy was validated in Jingye Lake at Tianjin University on April 30, 2022, and another experiment was conducted in Bohai Bay, Tianjin, on August 20, 2022, to assess the performance of a self-developed MG-Buoy for SSH measurement under real oceanic conditions. The experimental results indicate that the precision of single-frequency SSH measurement is 0.91 cm using the GNSS Post Processed Kinematic (PPK) technique with a single antenna, while the dual-frequency can achieve 0.50 cm accuracy. After adopting the Geometric Constraint method, the measurement accuracy of single-frequency and dual-frequency SSH values are 0.49 cm and 0.40 cm, respectively, representing a 46.2% and 20.0% improvements compared to the root mean square (RMS) value for the single GNSS antenna. Highlights: A low-cost GNSS buoy with four GNSS receivers has been designed for measuring sea surface height. A Geometric Constraint algorithm has been proposed to improve reliability of sea surface height measurements. The attitude error can be corrected based on multiple GNSS antennas.